SUBSIDENCE HISTORY AND HYDROCARBON MIGRATION MODELING IN SOUTH CASPIAN BASIN - Gahramanov, G.; Babayev М.; Shpyrko, S.; Mukhtarova, Kh. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
We study the mechanisms of migration and spacial distribution of hydrocarbon deposits along a regional 1000 km long SW - NE seismic cross section of the South Caspian Basin. A retrospective 2D geological simulation of basin subsidence and sediment filling history is performed taking into account accompanying processes of thermal and catagenetic transformations of organic matter, and subsequent migration and accumulation of hydrocarbons. The start of the basin opening with accumulation of considerable sedimentary mass can be dated as middle Mesozoic (Triassic or Jurassic), and hydrocarbon prone horizons can now be located at depths of 12 km. The hydrocarbon saturation of the Pliocene Productive Series is of epigenetic (allochtonous) nature, which is also confirmed in literature by geochemical data from mud volcanoes and by other facts. Geochemical age, depth of provenance and reworking degree of hydrocarbons point at generation sources in Mesozoic (gas) and Paleogene-Miocene formations (oil) with only subordinate participation of the lower "Productive Series" Pliocene suites. The dominant migration pattern of fluids is interformational (interstratal) intermittent injective subvertical flow along disjunctive planes, zones of increased fracturing and loose rocks, diapir intrusion contacts, eruptives of mud volcanoes, lithofacial unconformities and other structures, breaking the rocks continuity. This implies the possibility of commercial-scale accumulations of hydrocarbons at ultra high depths, if trap structures of sufficiently large sizes are available, comparable with already discovered giant oil and gas fields (Shah-Deniz, Azeri-Chirag-Gyuneshli etc).